Development of Arabic Learning Design Based on Higher Order Thinking Skill With Discovery Learning Model / Pengembangan Desain Pembelajaran Bahasa Arab Berbasis Higher Order Thinking Skill Dengan Model Discovery Learning Pada Siswa Kelas X SMKM 8 Paciran - Arif Widodo; Zakiyatul Abidah; Nurul Fahmi; Hana Chebaiki (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
The implementation of the 2013 curriculum demands the ability of teachers to train students to improve high-level thinking skills or higher-order thinking skills (HOTS), where students are required to be critical, creative, and innovative students in exploring complex experiences. To help students have high-level thinking skills, or HOTS needs to be supported by various learning models and expected to make the learning atmosphere enjoyable and change the learning conditions to be active and creative. This development research aims to: 1) Produce the design of learning Arabic based on Higher Order Thinking Skills with the Discovery Learning Skill; 2) Analyzing the effectiveness of the design. This research uses the research and development (R & D) method. The results of the study are as follows: 1) Discovery learning model on fiqh subjects based on cognitive learning theory through three stages: sensory representation (enactive), concrete representation (iconic), abstract (symbolic) representation, and constructivist theory with the student-centered learning approach. 2) The study results indicate that the discovery learning model meets the effective criteria seen from the point of view of achieving academic competencies. The results of the t-test showed significant differences between the pretest and posttest values of 12,05. As for the average of all validation instruments, 3,57 good categories and the average score of the observations in the first meeting of 3,48 were practical. Keywords: Discovery Learning, Higher Order Thinking Skill, Learning Design. مستخلص البحث يتطلب تنفيذ منهج 2013 قدرة المعلمين على تدريب الطلاب على تحسين مهارات التفكير العليا حيث يُطلب من الطلاب أن يكونوا طلابًا ناقدين ومبدعين ومبتكرين في استكشاف التجارب المعقدة. لمساعدة الطلاب على اكتساب مهارات تفكير عالية المستوى ومن المتوقع أن يكون الطالب قادرًا على جعل بئية التعلم ممتعًا ويمكنه تغيير ظروف التعلم ليكون نشطًا ومبدعًا. يهدف هذا البحث إلى: 1) إنتاج تصميم تعليم اللغة العربية بناءً على مهارات التفكير العالي باستخدام مهارة التعلم الاستكشافي, 2) تحليل فاعلية التصميم. يستخدم هذا البحث نموذج البحث التطويري. وأما نتائج البحث فهي : 1) نموذج التعلم بالاكتشاف في الفقه القائم على نظرية التعلم المعرفي من خلال ثلاث مراحل: التمثيل الحسي (النشط) ، التمثيل الملموس (الأيقوني) ، التمثيل المجرد (الرمزي) والنظرية البنائية مع التركيز على الطالب, 2) تشير نتائج البحث إلى أن نموذج التعلم بالاكتشاف يلبي المعايير الفعالة من جهة نظر تحقيق الكفاءات الأكاديمية. وأظهرت نتائج الاختبار t وجود فروق ذات دلالة إحصائية بين الاختبار القبلي والبعدي وذلك في 12.05. أما بالنسبة لتحقيق ​​جميع الأدوات، فقد كانت 357 فئة صالحة وكانت ​​درجات الملاحظات في الاجتماع الأول هي 3،48 وكانت في فئة عملية. الكلمات الرئيسية: التعلم بالاكتشاف ، التفكير العالي، تصميم التعليم